Eksplorasi Perbedaan Kecenderungan Belajar Siswa Laki-Laki dan Perempuan di Sekolah Dasar: Studi Kualitatif di SDN Kedoya Utara 01 Jakarta Barat - Yokha Latief Ramadhan; Faisal; Chaerudin Ahmad Alaziz (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to identify differences in learning styles between male and female students at SDN Kedoya Utara 01 West Jakarta. The study employed a descriptive qualitative approach involving three participants, consisting of one classroom teacher and two students (one male student and one female student). Data were collected through interviews and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that learning style differences are influenced by gender. Male students tend to demonstrate a dominant kinesthetic learning style, showing greater preference for physical activities and hands-on practice. In contrast, female students tend to exhibit visual and auditory learning preferences, such as taking notes, reading, and listening to teachers’ explanations. These findings are limited to the experiences of the participants involved and do not represent all elementary school students. Several factors were identified as influencing these differences, including psychological aspects, cognitive development, learning environment, interests, and family learning habits. The study implies that teachers need to implement varied instructional strategies to accommodate diverse student learning characteristics in elementary classrooms.